(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
The study aimed at evaluating the microbiological safety of vended foods in selected motor parks in Obio/Akpor Local Government Area, Rivers State, Nigeria. Forty-eight samples obtained from four motor parks (Choba, Rumuokoro, Eliozu and Oil-mill Park) were analyzed using standard microbiological methods for total heterotrophic bacteria count, virulent and antibiotic resistant profiles of Staphylococcus aureus and Escherichia coli. Total heterotrophic bacteria count ranged from 4.60 to 8.39 log10CFU/g. A total of 10 (20.83%) samples were positive for S. aureus while 14 (29.17%) were positive for E. coli. Total staphylococcal and Escherichia coli counts ranged from 4.89 to 7.01 and 2.70 to 5.31 log10cfu/g, respectively. Both bacteria were 100% resistant to augmentin. The confirmed E. coli showed varying resistant to cefixime (50%), ceftazidime (42.86%), cefuroxim (14.29%) and ofloxacin (7.14%); while S. aureus also showed varying resistant to erythromycin (10.00%), ceftriaxone (90.00%), cloxacillin (100.00%) and gentamycin (0.00%) The confirmed E. coli produced the expected bands for the E. coli attaching and effusing (eaeA), aggregative adherence fimbriae (aggR) and antimicrobial sensitivity testing (astA) virulence genes while S. aureus did not produce the expected bands with staphylococcal enterotoxin A (sea) and staphylococcal enterotoxin B (seb) genes. The detection of virulence gene bearing E. coli and multiple antibiotic resistant E. coli and S. aureus portends danger for commuters who patronizes these foods, hence the need for urgent public health interventions.